Trend Penelitian Penyelesaian Studi di Program Studi Teknologi Pendidikan Universitas Negeri Jakarta - Khaerudin (JTP - Jurnal Teknologi Pendidikan, 2019)
As an applied scientific discipline Educational Technology (ET) develops by utilizing and supported by other relevant sciences, such as psychology, communication, Information and Communication Technology (ICT), and education. Besides that as a science, Educational Technology is built on a clear foundation of ontological, epistemological, and axiological philosophy. This study aims to find empirical facts about the tendency of ET students to research their final project, viewed from three aspects, namely the paradigm and research methods used, and the ET area as the research domain. The research method used is quantitative descriptive research with a survey approach and is done through document analysis/content (content analysis). The documents analyzed were 577 scientific works, such as theses and dissertations. The results showed that research conducted by ET students of the Jakarta State University over the past 7 years tended to use qualitative research paradigms, research and development methods, and development areas.